RUSSIAN “SOFT POWER” IN THE NORTH-EAST AFRICA - Olga S. Kulkova (Politics and Religion, 2021)
The article builds on the Russian understanding of the “soft power” concept as a complex of tools and methods to reach the foreign policy aims through public diplomacy, information and communication technologies, humanitarian assistance and cultural initiatives, civil society interactions, and religious and inter-religious dialogues. “Soft power” tools are regarded as an addition to the traditional diplomatic methods. The article will critically consider the range of Russia’s contemporary “soft power” assets in its foreign policy dialogue with the countries of North and East Africa. The aim is to analyze the aspirations, implementation (during the last decade), results and further prospects of Russia’s “soft power” initiatives within and towards the indicated regions.